2003
DOI: 10.3758/bf03196101
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit processes in multicue judgment

Abstract: Expert judgment is often exercised in situations in which multiple pieces of information are available and relevant in varying degrees. For example, a doctor may be attempting to diagnose the likely illness of a patient on the basis of symptoms, medical history, clinical examination, and results of imperfectly diagnostic tests, as well as relevant demographic information, such as gender, age, and occupation. To take another example, a personnel manager might be judging the suitability of a candidate for a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 29 publications
0
38
1
Order By: Relevance
“…Reber et al, 1996), but also for individuals without neurological problems (e.g. Evans, Clibbens, Cattani, Harris, & Dennis, 2003;Gluck et al, 2002). In contrast, Lagnado et al (2006) found no evidence for a lack of task knowledge and self-insight.…”
Section: Implicit and Explicit Learningmentioning
confidence: 80%
“…Reber et al, 1996), but also for individuals without neurological problems (e.g. Evans, Clibbens, Cattani, Harris, & Dennis, 2003;Gluck et al, 2002). In contrast, Lagnado et al (2006) found no evidence for a lack of task knowledge and self-insight.…”
Section: Implicit and Explicit Learningmentioning
confidence: 80%
“…Although normative models propose that decisionmakers must weight cues by their objective validity, it has been shown time and again that this is a difficult undertaking (Evans, Clibbens, Cattani, Harris, & Dennis, 2003, Goodie & Crooks, 2004Permut, 1973;Peterson & Pitz, 1985;Tversky & Kahneman, 1974). In this paper, we have proposed that people will often weight information according to the ease with which it can be processed.…”
Section: Discussionmentioning
confidence: 99%
“…It seems highly doubtful that these various accounts can all be mapped onto each other or onto just two underlying cognitive systems (Evans, 2006a). It may be, for example, that parallel-competitive models will turn out to be appropriate in domains such as inductive rule learning (Sloman, 1996), multicue judgement (Evans, Clibbens, Cattani, Harris, & Dennis, 2003), and social cognition (Smith & DeCoster, 2000). There are a number of different kinds of implicit processes, with an important distinction being between those that deliver content for conscious processing (the main function of my proposed heuristic system) and those that can influence behaviour directly, without ever reaching consciousness-for example, through implicit learning or the acquisition of automated cognitive skills.…”
Section: Conflict In Dual Process Theories 335mentioning
confidence: 99%